An Efficient Rose Bengal Based Nanoplatform for Photodynamic Therapy. Issue 35 (12th August 2014) - Gianotti, Enrica; Martins Estevão, Bianca; Cucinotta, Fabio; Hioka, Noboru; Rizzi, Manuela; Renò, Filippo; Marchese, Leonardo
Abstract Organically modified mesoporous silica nanoparticles (MSNs) containing rose bengal (RB), a xanthene dye, were successfully synthesized. RB‐modified MSNs have shown a relevant photostability and a high efficiency in the photoproduction and delivery of singlet oxygen (1O2), which is particularly promising for photodynamic therapy (PDT) applications. In vitro tests have evidenced that RB‐MSNs are able to reduce cell proliferation in one of the most aggressive skin cancer types (SK‐MEL‐28) after green‐light irradiation.